Rutile compositions in the Kalgoorlie Goldfields and their implications for exploration - Scott, K.; Radford, N.; Hough, R.; Reddy, Steven (Taylor & Francis Co Ltd, 2011)
The compositions of 188 grains of rutile from 12 samples from the Kalgoorlie Goldfields, in the Yilgarn Craton of Western Australia, show that grains associated with the Mt Charlotte stockwork-style mineralisation have generally low minor-element contents (except for Fe, which may reflect, in part, ilmenite inclusions). However, rutile in the Fimiston (Golden Mile) lode-style mineralisation is (Fe + W)-rich, and in the high-grade Green Leader mineralisation rutile is (V + W)-rich. The incorporation of W6+ into the rutile structure in these styles of mineralisation is balanced by the presence of Fe3+ and V3+, although in rutile in the Green Leader mineralisation, V is present in both +3 and higher oxidation states. Detailed examination of W-rich rutiles from the Fimiston lode indicates that they have a complex internal microstructure, with variations in lattice orientation within single rutile crystals, probably caused by the strain associated with incorporation of large amounts of foreign ions into the rutile structure. The composition and complex microstructure of rutile can potentially discriminate between Au anomalies of higher and lower significance in the region (lode- vs stockwork-style), with the presence of V in high oxidation states suggesting that the hydrothermal fluids responsible were relatively oxidising.